Mode control in air gap dielectric resonant antennas for applications in IEEE 802.11ac wireless local area network base station antennas. Issue 12 (1st September 2015) - Chen, Zhijiao; Parini, Clive
Abstract : This study investigates the characteristics of air gap dielectric resonator antennas (AGDRAs), with emphasis on their radiating modes and potential applications for the up‐coming IEEE 802.11ac wireless local area network (WLAN) standard. An AGDRA differs from the conventional dielectric resonator antenna (DRA) by employing monopole supports to form an air gap between the dielectric resonator and the ground plane. This air gap offers more degrees of design freedom, wider bandwidth and a wider range of resonant modes, including the TE112 mode, which cannot be excited in the conventional rectangular DRAs. Four examples of AGDRA designs offering wide‐/dual‐band, dual‐/circular‐polarised and pattern reconfigurable were developed by exciting different modes. Good agreement between the simulated and measured results is observed, which proves the feasibility of AGDRA structures for the IEEE 802.11ac WLAN antennas.